2020
DOI: 10.2217/nnm-2019-0364
|View full text |Cite
|
Sign up to set email alerts
|

A Focus on The Genotoxicity of Gold Nanoparticles

Abstract: The comet assay is very simple and cost efficient, and is relatively sensitive for screening the genotoxicity of Au-NPs in in vitro and in vivo test systems. "

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Different types of micronuclei assays, such as cytokinesis-block micronucleus assay, mammalian erythrocyte micronucleus assay, and buccal micronucleus assay are considered for the assessment of NMs genotoxicity. The comet assay (CA), also known as single-cell gel electrophoresis (SSGE), is widely used for the assessment of AuNPs' genotoxicity by measuring DNA damage in eukaryotic and some prokaryotic cells [94]. The technique uses cells that are suspended in a thin agarose gel on a microscope slide.…”
Section: Immunotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of micronuclei assays, such as cytokinesis-block micronucleus assay, mammalian erythrocyte micronucleus assay, and buccal micronucleus assay are considered for the assessment of NMs genotoxicity. The comet assay (CA), also known as single-cell gel electrophoresis (SSGE), is widely used for the assessment of AuNPs' genotoxicity by measuring DNA damage in eukaryotic and some prokaryotic cells [94]. The technique uses cells that are suspended in a thin agarose gel on a microscope slide.…”
Section: Immunotoxicitymentioning
confidence: 99%
“…The European Medicine Agency (EMA) issued a guidance, and recommended standard genetic toxicology assays, both in vitro and in vivo, to determine the carcinogenic effects of pharmaceuticals [127]. Based on this recommendation, genotoxicity and mutagenicity may be assessed by the micronucleus test and comet assay, which are suitable to evaluate DNA damage [94,127]. Although these methods are not yet validated, authorities such as the EFSA promote them.…”
Section: Genotoxicity and Mutagenicitymentioning
confidence: 99%
“…This confirms the fact that AuNPs of size 50 nm possess the correct dimension to be easily internalized within the cell but without entering the nucleus and potentially causing genotoxicity. 30 , 39 , 40 Following the addition of NH 3 , shrinkage of the cell began to occur, as observed from Figure 2 b. Indeed, the vesicles containing AuNPs started to gather and move close to the nucleus, in concomitance with the cell shrinkage process.…”
Section: Resultsmentioning
confidence: 71%
“…Several studies have shown that zebrafish are a promising animal model for assessing NP toxicity due to their many advantageous characteristics, including a short lifespan and high reproductive capacity [33]. Various studies exhibited diverse reactions, and disparities among them can be attributed to various factors such as variations in the tested materials' characteristics (such as particle size and surface coating), discrepancies in NP concentrations, the use of different cell models, variations in testing protocols, discrepancies in genotoxicity endpoints, and differences in exposure durations [34].…”
Section: Metal Nanoparticlesmentioning
confidence: 99%